2016
DOI: 10.1007/s10461-016-1584-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Substance Use Disorders Among HIV Care Enrollees in the United States

Abstract: Prior efforts to estimate U.S. prevalence of substance use disorders (SUDs) in HIV care have been undermined by caveats common to single-site trials. The current work reports on a cohort of 10,652 HIV-positive adults linked to care at seven sites, with available patient data including geography, demography, and risk factor indices, and with substance-specific SUDs identified via self-report instruments with validated diagnostic thresholds. Generalized estimating equations also tested patient indices as SUD pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
109
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 76 publications
(71 reference statements)
7
109
3
Order By: Relevance
“…Cannabis use in other immunosuppressed populations and in those with other chronic conditions also appears to be higher overall than usage rates reported for the general public . However, comparisons with our data may be less relevant because most studies are not conducted in locales with available recreational cannabis and/or focus on diseases that are more frequently reported in younger patient populations (eg, inflammatory bowel disease) and/or may be associated with increased substance use (eg, human immunodeficiency virus) …”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Cannabis use in other immunosuppressed populations and in those with other chronic conditions also appears to be higher overall than usage rates reported for the general public . However, comparisons with our data may be less relevant because most studies are not conducted in locales with available recreational cannabis and/or focus on diseases that are more frequently reported in younger patient populations (eg, inflammatory bowel disease) and/or may be associated with increased substance use (eg, human immunodeficiency virus) …”
Section: Discussioncontrasting
confidence: 60%
“…[32][33][34] However, comparisons with our data may be less relevant because most studies are not conducted in locales with available recreational cannabis and/ or focus on diseases that are more frequently reported in younger patient populations (eg, inflammatory bowel disease) and/or may be associated with increased substance use (eg, human immunodeficiency virus). 35 Respondents in our cohort used cannabis for a wide variety of physical and neuropsychiatric symptoms that have a limited evidence base. 7,36,37 Most frequently, patients used cannabis to treat pain.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule and biologic therapies are in development for METH use disorder (3,4) and are being tested in human trials (5,6). Although preclinical studies have found that small molecule and biologic therapies are effective in healthy animal models, METH use is associated with a variety of comorbidities, such as HIV infection (7), hepatitis C infection (8), and polysubstance use with acetaminophen containing prescription opioid formulations (9). A common characteristic of these comorbid conditions is hepatic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…(Ives et al, 2006) Past history of cigarette, alcohol, and cannabis use are associated with risk of opioid misuse in those prescribed opioid analgesics (Fiellin, Tatrault, Becker, Fiellin, & Desai, 2014). This issue is particularly salient among HIV-infected individuals, who have a high prevalence of illicit drug use (Hartzler et al, 2017). Those who are prescribed opioid analgesics are at risk for misuse, addiction, or overdose; further, those who use opioid analgesics without a prescription or in ways other than how they are prescribed often use other illicit drugs such as cocaine or heroin as well (Ives et al, 2006).…”
Section: Introductionmentioning
confidence: 99%